The Rhetoric and the Reality The Mining Industry Is there a Gap between Policy and Reality? - Turnbull-Kemp, Maria (2013)
Mining is unavoidable, a resource which is fuelled by human consumption and necessity, a process that has adapted and undergone a revolution over the centuries but is still intrinsically dangerous, has a considerable impact on communities, the environment and has required the need for regulation. The shift in the mindset from society as a whole and the demands from stakeholders has forced the mining industry to act. This thesis will focus on Corporate Social Responsibility and the impact this phenomenon has had on the mining industry and whether the change in behaviour from two multinational mining organisations has made a positive impact on society, the environment and appeased the stakeholders.